Study on the 241Am-Be neutron reference radiation field established at CAEP - Zhang, Song; Ding, Da-Jie; Mao, Ben-Jiang; Zhuo, Ren-Hong; Cheng, Jing; Zheng, Hui; Lv, Ji-Lu; Liu, Yi-Xin (Radiation protection dosimetry, 2025)
In order to evaluate the field characteristics and instrument calibration capability of the 241Am-Be neutron reference radiation field at China Academy of Engineering Physics (CAEP), this paper conducted a series of researches on the radiation field. Firstly, the neutron energy spectrum of the field was investigated by multi-sphere spectrometer and Geant4. Secondly, the quantity transmission from China Institute of Atomic Energy (CIAE) to CAEP was achieved through the precision long counter system. In addition, three neutron dose rate meters from different manufacturers were calibrated in both the fields at CAEP and CIAE. Finally, the uncertainty of calibration factor for each instrument was calculated and validated in the two fields. The results demonstrated that the room scatter in the neutron radiation reference field at CAEP meet the requirement of ISO 8529 and the neutron energy spectrum measured in the field was acceptable. The range of neutron ambient dose equivalent rate that can be produced at CAEP and its uncertainty were determined. The calibration factors and their extended uncertainties obtained using two instruments in both fields were found to be reasonable and reliable. The radiation field established at CAEP can meet the routine calibration and experiment of common neutron dose rate meters.